Травма війни і лікування мовою в романі Володимира Рафєєнка "Мондеґрін (пісні про смерть та любов)" - Сидоренко, Оксана Василівна (My University, 2024)
With the beginning of the Russian aggression, a significant number of Ukrainians who had avoided communication in the Ukrainian language or had not considered it necessary to know it, distanced themselves from their national identity, began to activate the „dormant”, feeling the consequences and realizing the reasons for such a „rootless cosmopolitism”. The article analyzes the return to national roots on the example of Volodymyr Rafeenko's novel Mondegreen (Songs of Death and Love). The main character of the novel, Habinsky, an immigrant from Donetsk region, lived in Kyiv, consistently mastered the Ukrainian language, and it was under the influence of the change in linguistic self-expression that the personal content of the main character transformed. Habinsky's linguistic self-identification mobilizes narratives of historical memory, the attributes of which are national symbols, archetypes, and family memory.
War trauma and language treatment in Volodymyr Rafeenko’s novel Mondegreen (Songs of Death and Love)
Keywords: worldview paradigm; national identification; linguistic identification; historical memory; national symbols